2009
DOI: 10.1038/nature08512
|View full text |Cite
|
Sign up to set email alerts
|

HMGB proteins function as universal sentinels for nucleic-acid-mediated innate immune responses

Abstract: The activation of innate immune responses by nucleic acids is crucial to protective and pathological immunities and is mediated by the transmembrane Toll-like receptors (TLRs) and cytosolic receptors. However, it remains unknown whether a mechanism exists that integrates these nucleic-acid-sensing systems. Here we show that high-mobility group box (HMGB) proteins 1, 2 and 3 function as universal sentinels for nucleic acids. HMGBs bind to all immunogenic nucleic acids examined with a correlation between affinit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
513
1
5

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 602 publications
(532 citation statements)
references
References 33 publications
(64 reference statements)
13
513
1
5
Order By: Relevance
“…35,36 In the cytoplasm, HMGBs bind immunogenic nucleotides and deliver them to the cytosolic nucleic acid sensors retinoic acid-inducible gene I, MDA5, AIM2 and DAI and to the endosome nucleic acid-sensing TLRs (TLR3, TLR7 and TLR9). 7,10 Reports have also highlighted the interactions of HMGB1 with TLR9, retinoic acid-inducible gene I and TIM-3 10,37,38 and the vital role of HMGBs in autophagy regulation, 39 mitochondrial function and morphology [40][41][42] and cell proliferation. [43][44][45] Comparatively, an understanding of HMGBs in the nucleus is limited.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…35,36 In the cytoplasm, HMGBs bind immunogenic nucleotides and deliver them to the cytosolic nucleic acid sensors retinoic acid-inducible gene I, MDA5, AIM2 and DAI and to the endosome nucleic acid-sensing TLRs (TLR3, TLR7 and TLR9). 7,10 Reports have also highlighted the interactions of HMGB1 with TLR9, retinoic acid-inducible gene I and TIM-3 10,37,38 and the vital role of HMGBs in autophagy regulation, 39 mitochondrial function and morphology [40][41][42] and cell proliferation. [43][44][45] Comparatively, an understanding of HMGBs in the nucleus is limited.…”
Section: Discussionmentioning
confidence: 99%
“…In HMGB 2/2 mouse embryonic fibroblasts, the replication of vesicular stomatitis virus and vesicular stomatitis Virus 1 was increased and the expression of interferon-I was suppressed, which indicates that HMGB is critical for effective antiviral innate immune responses. 10 However, in influenza virus-infected cells, HMGB1 can promote viral growth through binding to the nucleoprotein component of influenza ribonucleoprotein. 13 Additionally, depending on the target cell and the microenvironment, HMGB1 may trigger or inhibit HIV-1 replication in vitro.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Extracellular HMGB1 functions as a proinflammatory cytokine-like molecule by direct binding to TLR4 or indirectly binding with other molecules (41). In addition, HMGB1 can play an intracytoplasmic role as a regulator between macroautophagy and apoptosis (11,(42)(43)(44) and a sentinel molecule for viral nucleic acid sensing (45).…”
Section: Discussionmentioning
confidence: 99%
“…Nucleic acid sensing within endolysosomes is thought to be a safety mechanism for self-nucleic acid, because self-nucleic acids are rapidly degraded by DNase and RNase before reaching endolysosomes. Self-derived nucleic acids, however, may reach endolysosomes in an inflammatory or autoimmune situation, where a variety of nucleic acid-binding proteins such as autoantibodies, anti-microbial peptide LL-37 [17], and a nuclear protein, high-mobility group box 1 protein [18], are complexed with host nucleic acids. We have recently demonstrated that host DNA complexed with Hsp90 stimulated TLR9 signaling, leading to robust IFN-α production [19].…”
Section: Introductionmentioning
confidence: 99%